Taxonomy of interactive computer-based visualisation systems and content for the mining industry – part 2 - Stothard, Phillip; Squelch, Andrew; Stone, R.; Van Wyk, E.; Kizil, M.; Schofield, D.; Fowle, K. (Maney Publishing, 2015)
This is the second paper of a series authored by a collaboration of international researchers. It develops taxonomy for computer-based virtual reality simulators of relevance to the mining industry. A summary is presented of simulator types implemented in the industry, and continuums are used to explain concepts and issues that affect simulator development and integration. The paper classifies simulators and demonstrates that there are potentially many simulator formats still to be realised and implemented by the mining industry. Simulator issues that are often overlooked such as human factors, cognitive load and development costs and their impact on the development of sustainable simulator technologies are considered in some detail. Barriers to development and integration are mentioned, and the need for industry to engage with university-level research and develop a uniform and integrated approach are discussed. Finally, a brief case study is presented and conclusions are drawn about the current status and sustainability of simulator development in the mining industry.